Blessed one Protestant perspectives on Mary - Gaventa, Beverly Roberts (Louisville Westminster John Knox Press, 2002)
Despite her prominence in the Christian narrative, Mary largely has been neglected within the Protestant church. Widely respected Protestant scholars seek to answer three basic questions: Who is Mary? How does Mary's story intersect with contemporary life: and What does Mary teach us about God? (October).
Keywords: Mary, -- Blessed Virgin, Saint. Theology of the Blessed Virgin Mary. Mary, -- Blessed Virgin, Saint -- Theology. Protestant churches -- Doctrines. Marie, -- Sainte Vierge -- Théologie.